Susta in able development in the model of anintegrated system of public education, creativity and humanistic learning - Tymoshenko, Yurii; Palamarchuk, Olha; Iehupov, Mykola; Dovbenko, Tetyana (My University, 2021)
In the context of ensuring an effective strategy for sustainable development, it is necessary to consider that modern education is mainly focused on the theoretical type of scientific knowledge, on natural and engineering-technological models of thinking. At the same time, the theory of pedagogy is constantly debated and criticized by scientism. It is a term that doesn’t exist in the European countries - humanitarian or humanistic technologies - it is like wooden iron, because both the humanitarian and humanistic paradigms were formulated and spread as an alternative to the technological direction, starting from it. This is a contradiction within the theory. Another contradiction: despite the frontal critique of the school of knowledge and subject-centrism, in practice such a subject-oriented or psychologically-oriented approach remains dominant. It is important to understand the reasons for this, otherwise we will not be able to find a practical way out of this situation, one criticism is not enough. This is not an internal pedagogical issue, but the convenience of management, external control over the activities of the education system, educational institution. Attempts to reform the pedagogical system constantly run into this circumstance, as pedagogy in its main part remains entirely state and regulated from the outside, no matter how much we talk about the partial autonomy of school education, higher education.
Tymoshenko Yu., Palamarchuk O.,Iehupov M.,Dovbenko T. Susta in able development in the model of anintegrated system of public education, creativity and humanistic learning / Yu. Tymoshenko., O. Palamarchuk, M. Iehupov and others // E3S Web of Conferences Sustainable Economy and Communities (24 June 2021). - 2021. - № 277. - Р.1-9.
Keywords: modern education; public education; humanistic learning; the European countries; students; higher education.; school education